Hypoxia Augments Cerebral Inflammation in a Dextran Sulfate Sodium-Induced Colitis Mouse Model - Han, Ying; Ding, Liping; Cheng, Xiang; Zhao, Ming; Zhao, Tong; Guo, Liang; Li, Xinyang; Geng, Yanan; Fan, Ming; Liao, Hong; Zhu, Lingling (Frontiers in Cellular Neuroscience, 2020)
The importance of hypoxia in the pathophysiology of inflammatory bowel disease (IBD) is increasingly being realized; in addition, hypoxia seems to be an important accelerator of brain inflammation, as has been reported by our group and others. IBD is a chronic intestinal disorder that leads to the development of inflammation, which is related to brain dysfunction. However, no studies have reported whether hypoxia is associated with IBD-induced neuroinflammation. Therefore, the objective of the present study was to determine whether hypoxia augments cerebral inflammation in a DSS-induced colitis mouse model. The mouse model was developed using 3% DSS for five days combined with exposure to hypoxic conditions (6000 m) for two days. Mice were randomly divided into four groups: control group, DSS group, hypoxia group and DSS plus hypoxia group. The results demonstrated that DSS combined with hypoxia resulted in up-regulation of colonic and plasmatic proinflammatory cytokines. Meanwhile, DSS plus hypoxia increased expression of Iba1, which is a marker of activated microglia, accompanied by increased expression of tumor necrosis factor alpha (TNF-a), interleukin-1β (IL-1β) and interleukin-6 (IL-6) in the brain. Moreover, the expression of tight junction proteins, such as zonula occludens-1 (ZO-1), occludin and claudin-5, was markedly downregulated. The current study provides new insight into how hypoxia exposure induces excessive inflammatory responses and pathophysiological consequences in the brain in a DSS-induced colitis model.